2023
DOI: 10.15273/hpj.v3i2.11553
|View full text |Cite
|
Sign up to set email alerts
|

Infographics and/or Pictograms and Medication Adherence: A Scoping Review

Abdullah Chanzu,
Molly Wells,
Natasha Vitkin
et al.

Abstract: Introduction: Medication adherence is the act of following medication instructions from a health care provider. Infographics and pictograms are visual science communication tools that have been shown to improve medication adherence. Objective: To synthesize and critically evaluate literature surrounding the use of infographics and pictograms in medication adherence. Methods: We conducted a literature search on PubMed, Ovid MEDLINE, CINAHL, Web of Science, and PsycInfo with the purpose of identifying literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In a healthcare setting, research has demonstrated that the use of pictograms can enhance patients' understanding, memory retention, and adherence to prescribed medications (Chanzu et al, 2023). The use of a visual approach can likely improve the medication labelling and the usability of the leaflets (Van Beusekom et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a healthcare setting, research has demonstrated that the use of pictograms can enhance patients' understanding, memory retention, and adherence to prescribed medications (Chanzu et al, 2023). The use of a visual approach can likely improve the medication labelling and the usability of the leaflets (Van Beusekom et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a healthcare setting, research has demonstrated that the use of pictograms can enhance patients' understanding, memory retention, and adherence to prescribed medications (Chanzu et al, 2023). The use of a visual approach can likely improve the medication labelling and the usability of the leaflets (Van Beusekom et al, 2018).…”
Section: Introductionmentioning
confidence: 99%